The Impact of Short-Form Video Advertisements on Digital Consumer Behavior: A Case Study of Restaurant and Food Advertising in Algeria - Soulef, Sahari; Imen, Bouchenkir; Guettaf, Lila; Khadidja, Abid (Journal of Ecohumanism, 2026)
This study aims to examine the influence of short-form video advertisements on digital consumer behavior, with a specific focus on restaurant and food-related advertising in the Algerian context. Adopting a descriptive-analytical research approach, the findings reveal that short-form video ads exert a statistically significant, moderately strong effect on digital consumer behavior. Based on these results, the study proposes several practical recommendations. Chief among them are: (1) refining digital targeting strategies to ensure advertisements reach audiences with a genuine interest in culinary experiences and dining, and (2) integrating elements of sustainability and corporate social responsibility into promotional content to reflect brand values and resonate with increasingly conscious digital consumers.